BYE, BYE DIRT: HEALTH PROMOTION AND HYGIENE FOR CHILDREN IN THE LANDFILL OF CODÓ : EXPERIENCE REPORT FROM STUDENTS OF THE PÍTAGORAS MEDICAL COURSE - Luz, Alan Luiz Portela Moura; de Sousa Coelho, Carlos Yann; dos Reis, Daniel Almeida; da Silva, Danilo Vieira; Sampaio, Francisco Augusto De Freitas; Dias, Hélio Silva; Silva, Hengrid Graciely Nascimento; Teixeira, Kayron Ruan Araújo (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Body hygiene is a set of behaviors that contribute to a healthier life. For children, learning these behaviors helps foster healthy development, providing physical and mental well-being and protecting against possible external agents. Objectives: To report on the experience of the university extension project “Bye, bye Dirt,” a project focused on health promotion and prevention through teaching proper hygiene practices. Methodology: This is a descriptive study in the form of an experience report, in which the “bye, bye, Dirt” extension project was implemented. The project was planned during the second semester of 2024 and executed on October 17 of the same year. Results: It was evident that the children actively engaged in the activities and showed enthusiasm, expressing interest in the topic and sharing how they practiced these hygiene habits daily for each discussed topic. Additionally, parents on-site welcomed the knowledge provided by the students, expressing gratitude for the university’s engagement with the community on such a relevant and necessary topic. Conclusion: Thus, the extension project proved to be a valuable social health tool, assisting an underserved community and improving the quality of life for those with limited access to information on proper hygiene practices.